2016
DOI: 10.1111/cen.13024
|View full text |Cite
|
Sign up to set email alerts
|

Low postoperative nonstimulated thyroglobulin as a criterion for the indication of low radioiodine activity in patients with papillary thyroid cancer of intermediate risk ‘with higher risk features’

Abstract: We conclude that in intermediate-risk patients 'with higher risk features', low nonstimulated Tg measured with a second-generation assay can be used as criterion for the administration of low (131) I activities (1850 MBq or less).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…In patients with PTC of low or intermediate risk submitted to total thyroidectomy who do not have circulating TgAb or neck US abnormalities, nonstimulated Tg ≤ 0·2 ng/ml measured with a second‐generation assay, instead of stimulated Tg < 1–2 ng/ml, has been accepted for the definition of an excellent response to initial therapy . In fact, previous studies have shown that stimulated Tg > 1–2 ng/ml is uncommon in patients with nonstimulated Tg ≤ 0·2 ng/ml and that the risk of recurrence is low in these individuals . However, stimulated Tg was obtained in most of the studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In patients with PTC of low or intermediate risk submitted to total thyroidectomy who do not have circulating TgAb or neck US abnormalities, nonstimulated Tg ≤ 0·2 ng/ml measured with a second‐generation assay, instead of stimulated Tg < 1–2 ng/ml, has been accepted for the definition of an excellent response to initial therapy . In fact, previous studies have shown that stimulated Tg > 1–2 ng/ml is uncommon in patients with nonstimulated Tg ≤ 0·2 ng/ml and that the risk of recurrence is low in these individuals . However, stimulated Tg was obtained in most of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Patients followed up at our institution from 2007 to 2013, who met the following criteria, were selected: (i) diagnosis of PTC (except for microcarcinoma restricted to the thyroid or the noninvasive encapsulated follicular variant), (ii) classified as low or intermediate risk according to the American Thyroid Association, (iii) submitted to total thyroidectomy with or without adjuvant therapy with 131 I, and (iv) excellent response to initial therapy (nonstimulated Tg ≤ 0·2 ng/ml, undetectable TgAb and neck US showing no abnormalities 12–18 months after thyroidectomy) …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Die gleiche Autorengruppe präsentierte eine zweite prospektive Studie mit 102 Patienten bei gleichem Risikoprofil, aber veränderten Bedingungen im Ausgangspunkt und im Endpunkt (31). Ausgangspunkt war das nicht-stimulierte Tg < 0,3 ng/ml vor der I-131 Ablation, Endpunkt ein nicht-stimuliertes Tg ≤ 0,2 ng/ml, entsprechend einer "exzellenten Response" nach ATA-Kriterien.…”
Section: A Ausgangspunkt Nichtstimulierter Tg-spiegel Vor I-131 Ablaunclassified